User acceptance toward mobile technology in healthcare / Bibiana Jikisai - Jikisai, Bibiana (Faculty of Computer and Mathematical Sciences, 2005)
The explosion of mobile communication and computing technologies in supporting highly specialized task and services in healthcare has made it increasingly important to identify the level of acceptance among healthcare practitioners and factors that may be influencing the level of their acceptance. The wide adoption of mobile technology can potentially improve the information access, enhance workflow and promote evidencebased practice to make informed and effective decisions at the point of care. This study will present the level of healthcare practitioners' acceptance toward the use of mobile technology in healthcare services. Other than that, this study also discussed about the benefits that gained by implementation of mobile technology in healthcare and what will influence the level of their acceptance. This study will use the extended TAM recommended by Wu, Wang and Lin (2005) in identifying the level of user acceptance. The result shows that compatibility and computer self-efficiency have significant effect on behavioral intent. There will be 4 factors that may influence the level of user acceptance which are, technical support and training, management support, compatibility and computer self-efficiency. Among these factors, compatibility has the strongest relationship to the behavioral intention.